Development of bacteria sensing platform through layered (metal-dielectric-metal) nanoparticles. (December 2019) - Patil, D.; Goswami, A.; Aravindan, S.; Rao, P.V.; Yoshino, M.
Highlights: Trilayer nanostructured (AuNPs-SiO2 -Au) bacteria sensing platform was fabricated. LSPR property of AuNPs is responsible for the sharp peaks appears in reflectance spectra. The developed platform is sensitive to the concentration of bacteria as spectral pattern changes with incubation time. Sharp shift in dip towards lower side of wavelength indicates the sensitivity of platform for the detection of S. aureus. Abstract: Trilayer possessing metal-dielectric-metal layer of nanometric thickness was prepared through multiple processes such as direct current (DC) and radio frequency (RF) Sputter Coating. This trilayer was used for a biosensing platform. Metal layer of gold having a thickness of 30 nm was deposited through direct DC Sputter Coating while the dielectric layer of SiO2 having a thickness of 177 nm was deposited through RF Sputter Coating. The trilayer coated sample was subjected to thermal annealing at 470 °C for 2 h in a temperature controlled furnace. The top layer of continuous gold film gets converted into randomly distributed gold nanoparticles (AuNPs) while the bottom gold layer undergoes minor morphological change. The reflectance spectrum of the dewetted trilayer is changed by presence of the Escherichia coli (E. coli) and Staphylococcus aureus ( S. aureus ) bacteria. The average reflectance of the as-deposited trilayer was found to be 60.06% while presence of E. coli and S. aureus on the trilayer reduces its reflectance to 21.84% and 47.58% respectively. The fabricated platform is more effective for the detection of S. aureus as it produced sharp detectable shift (70 nm to left) in spectra due to the spherical shape of bacterium. The shift in reflectance spectra depends on the incubation period which gives information about the amount of bacteria present on the platform.